2019
DOI: 10.1186/s12974-019-1631-0
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal injection of bone marrow stromal cells attenuates neuropathic pain via inhibition of P2X4R in spinal cord microglia

Abstract: BackgroundNeuropathic pain is one of the most debilitating of all chronic pain syndromes. Intrathecal (i.t.) bone marrow stromal cell (BMSC) injections have a favorable safety profile; however, results have been inconsistent, and complete understanding of how BMSCs affect neuropathic pain remains elusive.MethodsWe evaluated the analgesic effect of BMSCs on neuropathic pain in a chronic compression of the dorsal root ganglion (CCD) model. We analyzed the effect of BMSCs on microglia reactivity and expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 58 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Individuals may complain of concomitant positive (allodynia, paresthesias) and/or negative (impaired perception to various stimuli) somatosensory symptoms. Spinal cord microglia, a non-neuronal cell population, are in close neuroanatomical and neurochemical proximity with spinal cord neurons in terms of initiating and maintaining the neuropathic pain-associated hypersensitivity [ 39 , 40 , 41 ]. The relationship between the activity of several kynurenine pathway enzymes (IDO1/2, TDO, KMO, KYNU, and HAOO) and the development of neuropathic pain has been explored in a chronic constriction injury (CCI) rat model at the spinal cord and dorsal root ganglia (DRG) levels [ 42 ].…”
Section: Kynurenine Pathway In the Pathogenesis Of Neuropathic Paimentioning
confidence: 99%
“…Individuals may complain of concomitant positive (allodynia, paresthesias) and/or negative (impaired perception to various stimuli) somatosensory symptoms. Spinal cord microglia, a non-neuronal cell population, are in close neuroanatomical and neurochemical proximity with spinal cord neurons in terms of initiating and maintaining the neuropathic pain-associated hypersensitivity [ 39 , 40 , 41 ]. The relationship between the activity of several kynurenine pathway enzymes (IDO1/2, TDO, KMO, KYNU, and HAOO) and the development of neuropathic pain has been explored in a chronic constriction injury (CCI) rat model at the spinal cord and dorsal root ganglia (DRG) levels [ 42 ].…”
Section: Kynurenine Pathway In the Pathogenesis Of Neuropathic Paimentioning
confidence: 99%
“…Then, cellular samples containing 30 μg of protein and tissue samples containing 60 μg of protein were separated by SDS-PAGE before being transferred to PVDF membranes. Western blot was performed using standard protocols as we previously described [ 29 ]. Membranes were blocked with 5% (w/v) milk (Bio-Rad) in TBS with 0.05% Tween 20 (TBST) for 2 h at room temperature and then incubated with the appropriate primary antibodies overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In their experiment, stem cells inhibited the core pain signal pathway of P2X4R in microglia and reduced the expression of P2X4R. However, it was found that the number of activated microglia was not affected by IBA labeling of microglia [ 66 ]. Compared to the previous three-week studies, the results from Teng et al were taken from the chronic compression of the dorsal root ganglion model (CCD) six days after stem cell therapy.…”
Section: The Role Of Stem Cells In the Spinal Mechanismmentioning
confidence: 99%